2018
DOI: 10.1155/2018/2695025
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Layer Optimal Dispatching Strategy for Microgrid Energy Management Systems considering Demand Response

Abstract: The continuous development of microgrid’s technology creates favorable conditions for the access of distributed energy. Firstly, in order to consider the interests of the demand side and the power side, this paper presents a dual-layer optimal dispatching model of microgrid based on demand response. The objective of the first-layer optimization is to obtain the maximum load satisfaction and to optimize the load curve. The objective of the second-layer optimization is to make the microgrid system economical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The EMS unit manages the energy flow from the sources through information such as load demand forecasting while ensuring the load demand of the community microgrid and reducing operational costs [25]. Fig.…”
Section: Energy Managementmentioning
confidence: 99%
“…The EMS unit manages the energy flow from the sources through information such as load demand forecasting while ensuring the load demand of the community microgrid and reducing operational costs [25]. Fig.…”
Section: Energy Managementmentioning
confidence: 99%
“…As mentioned, This time, focus has been prioritized in determining the energy source type, energy management system (EMS) approach, control strategies adopted and the involvement of demand response in the MG system. From the study, it has been found that there are eleven papers [61][62][63][64][65][66][67][68][69][70][71] have strong connections to the searched key points. As the results, summarization on this work is demonstrated in Table 4.…”
Section: Research On Mg's Energy Management and Controlmentioning
confidence: 99%
“…The operational cost and pollutants emission from the microgrid are minimized considering the incentive responsive loads and solved by the mixed integer linear programming technique using CPLEX solver of the GAMS software. In Pan et al, 18 an optimization based on financial cost and load satisfactory is considered with the assumption of the demand response existence in the microgrid. Two demand response programs based on TOU and RTP are integrated into the optimal scheduling model and the developed model is solved using a meta-heuristic algorithm under uncertainties of DGs and loads in Nikmehr et al 19 Hong's 2m point estimate method is used in Gazijahani and Salehi 20 with considering incentive-based DR and reconfiguration scheduling to minimize the operation cost of the microgrid.…”
Section: Introductionmentioning
confidence: 99%